Microplastic Monitoring at Different Stages in a Wastewater Treatment Plant Using Reflectance Micro-FTIR Imaging - Tagg, Alexander S.; Sapp, Melanie; Harrison, Jesse P.; Sinclair, Chris J.; Bradley, Emma; Ju-Nam, Yon; Ojeda, Jesús J. (Frontiers in Environmental Science, 2020)
While the presence of microplastics has been reported in aquatic habitats across the globe, the pathways through which they enter the environment are still poorly understood. Studies investigating the fate of microplastics in wastewater are gaining attention but are still scarce, despite the urgent need to understand the role of wastewater treatment plants (WWTP) as point sources of aquatic microplastic pollution. A likely reason for the limited number of WWTP-associated studies is that working with a biogenic organic matter (BOM)-rich sample matrix like wastewater is challenging. Here, we investigated the presence of microplastics (MP) throughout several stages of a wastewater treatment plant (WWTP) at multiple depths, employing Fenton’s reagent and focal plane array-based reflectance micro-Fourier-transform infrared spectroscopic (FPA-based reflectance micro-FTIR) imaging, a protocol that allows the automated detection and identification of microplastics in complex samples with high organic matter content, without the need for previous visual sorting, or reducing considerably the thickness of the sample, or the use of IR-transparent transmission windows. It was found that the number of microplastic fragments detected at downstream stages of the WWTP notably decreased following the primary settlement stage, with primary settlement stage samples responsible for 76.9% of total microplastics detected. Despite the marked reduction in the number of microplastic particles following the primary settlement stage, an average total of 1.5 MP L-1 were identified in the final effluent of the WWTP.